2016
DOI: 10.21276/ijmrp.2016.2.3.030
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicohistopathological Correlation of Hysterectomy Specimens in Kashmiri Women Undergoing Elective Abdominal Hysterectomy in a Tertiary Care Centre

Abstract: To study clinical features, indications and histopathological diagnosis of elective abdominal hysterectomy in our region. Patients and Methods: Patients presenting to our department were worked up for age, presenting symptoms, indications for hysterectomy and histopathology reports of the specimens were analysed. The study was done over a period of two years. Results: A total of 237 elective abdominal hysterectomies were performed. About 99% of indications of hysterectomy were for benign disease. Peak age inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Saleh SS et al found around 40% of patients having heavy menstrual flow. 13 Similar results were shown by Saldanah CL et al 14 The reason behind may be due to noncompliance with the medical therapy. The next common symptom was pain abdomen which was also observed in other studies done in Nepal.…”
Section: Discussionsupporting
confidence: 67%
“…Saleh SS et al found around 40% of patients having heavy menstrual flow. 13 Similar results were shown by Saldanah CL et al 14 The reason behind may be due to noncompliance with the medical therapy. The next common symptom was pain abdomen which was also observed in other studies done in Nepal.…”
Section: Discussionsupporting
confidence: 67%